Revitalisasi Pendidikan Kewarganegaraan untuk Meningkatkan Civic Engagement dalam Gerakan Sustainable Development Goals (SDGs): Revitalizing Citizenship Education to Increase Civic Engagement in the Sustainable Development Goals (SDGs) Movement - Ahmad Muhamad Mustain Nasoha; Afifah Nur Khusna; Nayla Damayanti (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Amidst rising intolerance, moral decline, low social solidarity, and a national identity crisis, reforming Civics Education (PKn) has become an urgent need to restore the nation's identity based on the values of Pancasila. PKn aims not only to instill an understanding of laws and norms, but also to develop character, integrity, responsibility, and social empathy. This renewal process involves innovations in orientation, methods, and learning practices that are more contextual and interactive, and capable of increasing social awareness and active student involvement in national life. There is a close relationship between the revitalization of Civics and the Sustainable Development Goals (SDGs) because both share the same goal: building a peaceful, just, inclusive, and sustainable society. Civics plays a crucial role in helping achieve several SDG goals, such as quality education, reducing inequality, addressing climate change, and strengthening global peace and cooperation. Through an approach that emphasizes civic engagement, Civics encourages students not only to understand their rights and obligations but also to actively participate in social, political, and environmental issues. The choice of the theme of revitalizing Civics (PKn) to increase civic engagement in the SDGs movement is based on the challenge of declining community participation, especially among the younger generation, who are becoming indifferent to national issues. Furthermore, the development of digitalization has changed moral values and nationalism, so Civics must adapt to create critical and responsible digital citizens. With the revitalization of Civics based on the values of Pancasila and the spirit of the SDGs, education can function as a transformative force in shaping a generation of quality, critical thinkers, empathizers, and committed to peace and social justice both at the national and global levels.